Pengaruh Gaya Kepemimpinan Dan Budaya Organisasi Terhadap Produktivitas Karyawan Departemen Cutting Pada PT. Knh Garmindo Jaya Bogor - Sesilia Susisusanti Ndruru; Lilis Suryani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. The purpose of this study was to determine the Leadership Style and Organizational Culture on Employee Productivity in the Cutting Department at PT KNH Garmindo Jaya Bogor. The method used is quantitative. The sampling technique used saturated sampling and obtained a sample of 50 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing test with the help of SPSS software version 27. The results of this study are leadership style has a significant effect on employee productivity with a coefficient of determination of 58.5%; and hypothesis testing is obtained t arithmetic > t table or (8,227 > 2,010). Organizational culture has a significant effect on employee productivity with a coefficient of determination 62.4%; and hypothesis testing is obtained t count > t table or (8,926 > 2,010). Leadership style and organizational culture simultaneously have a significant effect on employee productivity with the regression equation Y = 4,476 + 0,340X1 + 0,421X2. The value of the coefficient of determination is 66.6% while the remaining 33.4%; is influenced by other factors. Hypothesis testing is obtained by the calculated F value > F table or (46,944 > 2,802).